ONLINE LEARNING MANAGEMENT OF PASTRY COURSES ON COMPETENCY ACHIEVEMENTS DURING THE COVID 19 PANDEMIC - Ezi Anggraini; M Giatman; Hasan Maksum (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2022)
After the spread of the Covid-19 outbreak had an effect on the world of education, changes to the learning system were directed to an online home study policy. This study aims to determine the effect of online learning management on competency achievement in the Pastry course. This research method uses a quantitative method by comparing student learning outcomes online during the pandemic and before the pandemic in the Pastry course at the IKK FPP UNP department. The Pastry course is a basic practical course that requires more direct lecturer guidance. Based on the comparison of the average value of learning outcomes, it shows that the class that does face-to-face learning has an average value of 8.8 with a standard deviation of 8.52775. Meanwhile, classes that do learning with online or online media have an average of 7.5 and a standard deviation of 7.52775. This shows that the average value with face-to-face learning has an average higher than when using online learning using the e-learning classroom application. It turns out that management for pastry colleges is better using face-to-face learning.